2019
DOI: 10.1016/j.bja.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

An automated machine learning-based model predicts postoperative mortality using readily-extractable preoperative electronic health record data

Abstract: Background: Rapid, preoperative identification of patients with the highest risk for medical complications is necessary to ensure that limited infrastructure and human resources are directed towards those most likely to benefit. Existing risk scores either lack specificity at the patient level or utilise the American Society of Anesthesiologists (ASA) physical status classification, which requires a clinician to review the chart. Methods: We report on the use of machine learning algorithms, specifically random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 26 publications
3
90
0
1
Order By: Relevance
“…Due to COVID-19 restrictions, the selection meeting of the IMIA Yearbook Editorial Committee was held as a videoconference on Apr 17, 2020. In this meeting, three papers [6][7][8] were finally selected as best papers for the CIS section (Table 2). A content summary of these three CIS best papers can be found in the appendix of this synopsis.…”
Section: About the Paper Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to COVID-19 restrictions, the selection meeting of the IMIA Yearbook Editorial Committee was held as a videoconference on Apr 17, 2020. In this meeting, three papers [6][7][8] were finally selected as best papers for the CIS section (Table 2). A content summary of these three CIS best papers can be found in the appendix of this synopsis.…”
Section: About the Paper Selectionmentioning
confidence: 99%
“…All three of the best papers in the CIS section can be assigned to these two clusters. The contribution by Brian L. Hill and colleagues [8], who successfully created a fully automated machine-learning-based model for postoperative mortality prediction is in the yellow cluster. We selected this paper from the British Journal of Anaesthesia as the approach is innovative, uses only preoperative available medical record data, and can better predict in-hospital mortality than other state-of-the-art methods.…”
Section: Findings and Trends In 2019mentioning
confidence: 99%
“…We and others have recently shown that deep neural networks (DNNs) and random forest algorithms, using only readily available information extracted from the electronic health record before or at the end of surgery, can successfully predict postoperative inhospital mortality with area under the curve (AUC) ranging from 0.87 to 0.93 [1][2][3] . While DNNs and other machine learning models often have higher accuracy than simpler models like logistic regression (LR), they are often considered to be "black box" models and this lack of interpretability and transparency is considered a challenge for clinical adoption 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Risk scores commonly used for surgical patients (i.e., ASA, APACHE, P‐POSSUM) have substantial limitations when applied to elderly patients: (I) they were built and validated in past decades mainly on young adults; (II) they consider one single organ function at a time, and (III) they do not estimate the patient's physiologic reserve, functional, cognitive, and social factors, which are all recognized as relevant outcome determinants in geriatric medicine 7 . Thus, despite the widespread adoption of these scores, their ability to predict complications appears low among elderly CRC patients scheduled for surgery 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, despite the widespread adoption of these scores, their ability to predict complications appears low among elderly CRC patients scheduled for surgery. 8 The comprehensive geriatric assessment (CGA) is the "evidencebased" reference tool to assess the overall health of elderly patients. 9,10 CGA is usually delivered by a multidisciplinary team led by a geriatrician alongside specialist nurses, physiotherapists, occupational therapists, and social workers.…”
Section: Introductionmentioning
confidence: 99%